Way of determination of parameters of rheological model of soil layer by experimental creep curve of layer - Kendzera, O.V.; Rushchitsky, J. J. (Reports of the National Academy of Sciences of Ukraine, 2023)
A method of determining the parameters of the standard three-constant rheological model is proposed, which is recommended to be applied to the description of the seismic waves in soil layers. The standard model is briefly described. Also, the essence of the method is outlined. The feature of this method is that it is enough to have one experimental creep curve of the soil layer to determine the three rheological parameters of the wave model. Some peculiarities of the approach are commented on.